Pengaruh Penerapan Manajemen Resiko Terhadap Fleksibilitas Pada Bank Umum Yang Terdaftar di Bursa Efek Indonesia 2013-2017 - Hilda Octavana Siregar; Faridiah Aghadiati Fajri (EBBANK, 2018)
This study aims to determine the implementation of management risk affecting financial flexibility at banking. Banks are institutions that maintaining the financial stability of a country through an intermediary role.  The role of intermediation is the role of finding between parties who have funds and those who need them. Under this condition, banks have a big risk because the impact of failure in management can result in many parties. The risk is liquidity risk, credit risk and operationa risk. Risk management can avoiding bankcrupty and financial problem. Financial flexibility is when companies can make various attractive investments that are able to bring in income or be able to pay obligations at any time. Thi study is quantitative method with stastistic descriptive logistic regression. The data used are bank financial report data listed on the Indonesia Stock Exchange in 2013-2017. The research result is implemention risk management can effecting signicantly financial flexibility. But operational risk has no effecting to financial flexibility